Contemporary nanocellulose-composites: A new paradigm for sensing applications. (15th December 2022) - Kumar, Sanjay; Ngasainao, Moses Rinchui; Sharma, Deepa; Sengar, Manisha; Gahlot, Ajay Pratap Singh; Shukla, Samarth; Kumari, Pratibha
Abstract: Nanocellulose (NC) is the biological polymeric nanomaterial booming in the international market. The burgeoning demand for cellulose materials and advancements in nanotechnology have intensified the researches on the development of cellulose-based nanomaterials. Substantial research on nanocellulose-based composites in energy, electronics, biomedical, health, and the environment has been carried out in the last few decades. NC offers a plethora of outstanding properties such as biodegradability, renewability, and excellent fibrous structure. The recent advancement in the synthetic methodologies for various types of nanocellulose materials and their applications in a myriad of fields such as biosensing, chemical sensing, gas sensing, and strain sensing have been explored. The surface modification ability and robust nature of NC offer various possibilities for hybrid materials in the sensing field. Many sensors developed on plastic, paper, and glass platforms will be replaced with NC to modify the conventional sensing probes in the near future. Graphical abstract: Unlabelled Image